Dementia, Treatment Decisions, and the UN Convention on the Rights of Persons With Disabilities. A New Framework for Old Problems - De Sabbata, Kevin (Frontiers in Psychiatry, 2020)
The UN Convention on the Rights of Persons with Disabilities has been at the center of considerable debate in the field of mental health. The discussion has caught up in particular after the publication of General Comment No. 1 in which the Committee on the Rights of Persons with Disabilities proposes a particularly radical interpretation of Article 12 of the Convention. Such a document has triggered skeptic and at times hostile reactions especially by psychiatrists, together with some positive comments. In this context, there is sometimes the tendency to focus only on the problematic aspects of the rights and support based model proposed by the CRPD and its Committee, forgetting that also “pre-CRPD” legislations on legal capacity present significant shortcomings. In this contribution I focus on the paradigmatic case of treatment decisions of people living with dementia with the aim to show how a number of provisions emerging from the CRPD and General Comment No. 1 can contribute to overcome the issues characterizing the traditional model of legal capacity and consent to treatment. First, I provide a brief overview of the provisions contained in the CRPD and General Comment No.1, summarizing the debate in this area. Then, I move to the case of treatment decisions of people living with dementia, analysing the main issues posed by the traditional model of capacity still characterizing European legislations. I will show how such problems and the solutions previously advanced by academics and practitioners resound in many ways with those identified by the CRPD and its Committee. In the second part, I analyse one by one the main provisions proposed by the CRPD and the Committee, studying how they can be applied in the area of treatment decisions of people living with dementia. In this context I point out the possible interpretations of the various provisions and their pros and cons, also referring to ongoing initiatives providing an insight on how such norms might work in practice.